2005
DOI: 10.1038/nsmb958
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition of X11/Mint scaffold proteins revealed by the closed conformation of the PDZ tandem

Abstract: Members of the X11/Mint family of multidomain adaptor proteins are composed of a divergent N terminus, a conserved PTB domain and a pair of C-terminal PDZ domains. Many proteins can interact with the PDZ tandem of X11 proteins, although the mechanism of such interactions is unclear. Here we show that the highly conserved C-terminal tail of X11a folds back and inserts into the target-binding groove of the first PDZ domain. The binding of this tail occludes the binding of other target peptides. This autoinhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 48 publications
7
85
0
Order By: Relevance
“…It has been reported that tandem PDZ domains can form supramodules by direct inter-PDZ domain interactions, and such tandem PDZ supramodules include the PDZ12 and PDZ45 tandem from GRIP family proteins, the PDZ12 tandem from X11/Mint family proteins (23), and the PDZ12 tandem from syntenin (24) (Fig. S5B and C).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that tandem PDZ domains can form supramodules by direct inter-PDZ domain interactions, and such tandem PDZ supramodules include the PDZ12 and PDZ45 tandem from GRIP family proteins, the PDZ12 tandem from X11/Mint family proteins (23), and the PDZ12 tandem from syntenin (24) (Fig. S5B and C).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the PDZ2 domain of APBA1 (also known as X11/MINT) contains a deletion of the same magnitude as the ZO-1 PDZ2 sequence. However, the NMR structure of this domain (Protein Data Bank code 1U39) reveals a monomeric PDZ domain (33), albeit with a rather short ␤2 and ␤3 strands, which are connected by a tight turn. Likewise, the second PDZ domain of SDCB1 (syntenin-1) is monomeric (34), despite having a comparable deletion in this region in comparison to ZO-1 PDZ2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous NMR studies observed intramolecular contacts between the Mint1 C-terminal tail and the PDZ1 domain, which blocks its ability to bind exogenous targets (25). Phosphorylation of a Tyr residue at the penultimate position in the C-terminal tail was proposed to disrupt its association with the PDZ1 domain, thereby liberating the PDZ1 domain to engage other ligands (25). Our data now show a different type of intramolecular inhibition within Mint1 whereby the region C-terminally adjacent to the Mint1 PTB domain forms an α-helix that occludes the APP binding site.…”
Section: Discussionmentioning
confidence: 99%